Pembuatan dan Pendampingan SI MBEK: Sistem Informasi Monitoring Pembesaran Kambing di Desa Rukti Endah - Yulianti, Titin; Purwiyanti, Sri; Komarudin, Muhamad; Septama, Hery Dian; Sianipar, Yos Marison; Utami, Elika Dwi; Pangestu, Rizki (Journal of Appropriate Technology for Community Services, 2025)
Rukti Endah Village is a village that is part of the administrative area of Seputih Raman sub-district, Central Lampung Regency. Rukti Endah Village has enormous livestock potential with a village area of 800 hectares where the majority of people are livestock breeders and farmers. One of the livestock MSMEs in Rukti Endah Village is CV Raman Farm Sejahtera, known as Raman Farm. Raman Farm facilitates livestock groups in the area to develop livestock care businesses called Hotel Ternak. The Hotel Ternak accepts care for livestock by customers to be raised until they are ready to be sold, one of which is goats. The more customers and livestock they entrust, the more difficult it is to manage the development history of each livestock. Apart from that, to expand the business network, customer trust is needed through more professional business management by utilizing information system technology. This activity aims to create an information system for monitoring goat enlargement including the health history of goats which is named the Goat Enlargement Monitoring Information System (SI MBEK) using the Rapid Application Development (RAD) system development method by means of iterative development, providing assistance and management training and use of goat farming information systems and carry out activity evaluations. The method for implementing community service used is Participatory Rural Appraisal (PRA) in which partners actively participate in this activity. The result of this community activity was the construction of SI MBEK. The application of SI MBEK can increase effectiveness in managing livestock hotels for rearing goats. Because it uses the RAD-iterative development model, SI MBEK can continue to be developed into the second version and beyond by adding features according to further needs.